Ewangelizacja w kontekście kultury górskich rejonów Papui–Nowej Gwinei. Część 1 - Kajzer, Dariusz (Annales Missiologici Posnanienses, 2021)
The purpose of the article is to show the dynamics of evangelization in the context of the culture of the peoples living in the mountainous areas of Papua New Guinea. The starting point is the history of Christianization of these areas and the rooting of Churches of various denominations there. The analysis reveals the tools of evangelization used by Catholic missionaries to penetrate the culture and traditions of the locals, which resulted in the formation of new Christian communities.